2000
DOI: 10.1021/jf000054s
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin-Sensitized Photochemical Changes in β-Lactoglobulin in an Aqueous Buffer Solution as Affected by Ascorbic Acid

Abstract: The effects of ascorbic acid on the riboflavin-sensitized photochemical changes in beta-lactoglobulin in an aqueous buffer solution as determined by high performance gel permeation liquid chromatography (HPGPLC), insoluble protein content, and individual amino acid content during fluorescent light illumination were studied. The riboflavin-sensitized photochemical degradation of beta-lactoglobulin was effectively inhibited by ascorbic acid, and its inhibitory effectiveness was concentration dependent. The 0.1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Dalsgaard et al (2007) recently studied the changes in the structure of milk proteins upon photo-oxidation and elucidated that the vulnerable amino acids mentioned before were oxidized to protein carbonyls and dityrosine resulting in the aggregation of a-and b-caseins. Light-induced changes in the structure of milk proteins were also reported by Jung et al (Jung et al 2000) who illuminated b-lactoglobulin. It has already been suggested that these changes will have their consequences on the biological activity: however, to which extent is still unknown (Chatterton et al 2006;Korhonen et al 1998).…”
Section: Introductionmentioning
confidence: 57%
“…Dalsgaard et al (2007) recently studied the changes in the structure of milk proteins upon photo-oxidation and elucidated that the vulnerable amino acids mentioned before were oxidized to protein carbonyls and dityrosine resulting in the aggregation of a-and b-caseins. Light-induced changes in the structure of milk proteins were also reported by Jung et al (Jung et al 2000) who illuminated b-lactoglobulin. It has already been suggested that these changes will have their consequences on the biological activity: however, to which extent is still unknown (Chatterton et al 2006;Korhonen et al 1998).…”
Section: Introductionmentioning
confidence: 57%
“…As reported by Lee et al (1998), who demonstrated that addition of 0.1% ascorbic acid resulted in 50% and 25.5% inhibition of reduction of riboflavin in whole milk and skim milk, respectively, after 10 h light illumination at 3300 lux. In another study, Jung et al (2000) observed that addition of 0.1% ascorbic acid (approximately 5 mM) has a positive effect on the riboflavin-sensitized photo-chemical changes in milk protein degradation. Notably, in this study, the protective effect of 5 mM ascorbic acid was less than that of 1 mM AR.…”
Section: Article In Pressmentioning
confidence: 94%
“…has strong quenching ability against active-oxygen species and effectively prevents the light-activated off-flavour formation and reduction of riboflavin in milk and aqueous solution (Jung, Lee, & Kim, 2000;Lee et al, 1998). In addition, Pischetsrieder et al (1998) also reported that AR showed antioxidant activity that was very similar to that of ascorbic acid.…”
Section: Article In Pressmentioning
confidence: 96%
“…The ROS include OH (hydroxyl radical), hydrogen peroxide, superoxide anion, peroxyl radical, and singlet molecular oxygen. Among these ROS, singlet molecular oxygen has aroused much interest as a biological oxidant owing to its unique oxidant properties and its extremely high reactivity with biological components such as proteins, lipids, vitamins, and DNA (Foote 1976; Linetsky and Ortwerth 1997; Jung and others 1998; King and Min 1998; Jung and others 2000; Choe and Min 2005). Not like other ROS, singlet oxygen is an electronphilic nonradical type ROS (Min and Boff 2002; Choe and Min 2005).…”
Section: Introductionmentioning
confidence: 99%